Determinación un método eficiente para la extracción de saponinas producidas durante el lavado de quinua (chenopodium quinoa) y su uso como tensoactivo en la elaboración de champú - Trujillo Andino, Natalie Mishell (2017)
Quinoa has been used for human food before the Spanish conquest. Rinsing the quinoa is the traditional and essential method to make it suitable for the food consumption; this process eliminates saponins, which are considered as a waste. In Ecuador there is an important demand for cosmetics such as shampoo, however the elaboration of this type of products is based on the use of surfactants to improve the appearance of them. The present titration work has the purpose of optimizing a method for the extraction of saponins in the rising of quinoa and to evaluate its capacity as a surfactant in shampoo. For methodology development 5 treatments had been used (T1, T2, T3, T4, T5) and a saponin-free pattern (T0) were performed. (1.68 more or less 0.18 mg) of saponin was obtained at 50 °C and 5 minutes by the Rising method. The evaluation of the surfactant capacity of the saponins yielded the following results: T4 (0.59 v 0.26 mg of saponins) had a pH of 7.73. T5 (1.68 more or less 0.18 mg of saponins) obtained 77 more or less 1 mm of foam in the first measurement and (75.89 more or less 0.51 mm) after 5 minutes. T5 (1.68 more or less 0.18 mg of saponins) had a viscosity of 2551.33 more or less 1.22 cP, at a rate of 50 rpm. The project of shampoo chemical surfactant free is profitable with a NAV of $ 127041, a B/C of $ 1.80, TIR of 47.89 percent and a WACC of 26 percent.